The critical efforts of Lady Sukayna bint al-Husayn (peace be upon her) in her private critical council - قادر, فاضل محمد (Sulaimani Journal for Humanities, 2020)
The most important point in the research is shed lighting on the efforts of the late critic lady (Sukaina Hussein) who was interested in of great education and critical analysis that help us to feel the poets' intentions and she was evaluating the poems by encouraging them and declaring the mistakes either individually or in public. She used the hold meeting with a large number of the poets like (Jarir, Alfarazdaq, Jameel, Nasib, and others). She in her theses has shown many of the critical rules which the poets must follow and take into consideration